Polyaniline-decorated hyaluronic acid-carbon nanotube hybrid microfiber as a flexible supercapacitor electrode material. (15th April 2020) - Zheng, Ting; Wang, Xiaodong; Liu, Yingyi; Bayaniahangar, Rasoul; Li, Hongbin; Lu, Chunrui; Xu, Nuo; Yao, Zhaoding; Qiao, Yingjie; Zhang, Dongxing; Pour Shahid Saeed Abadi, Parisa
Abstract: Continuing miniaturization of flexible electronics demands the generation of microscale fiber-shaped supercapacitor electrodes with high mechanical flexibility and durability, charge-discharge rate, and cycling stability. For this purpose, here, a novel nanostructured microfiber is fabricated from hyaluronic acid (HA), carbon nanotubes (CNTs), and polyaniline (PANI) by a combination of wet spinning and electrochemical polymerization. The obtained core-shell HA/CNT/PANI fibers show an average six fold increase in specific capacitance compared to HA/CNT fibers and approximately 90% capacitance retention over 3000 cycles at 100 mV s −1 . The cycling stability is higher than that reported for PANI without the HA/CNT core. In addition, the core-shell HA/CNT/PANI microfiber displays excellent flexibility and electrochemical cycling stability under bending and twisting, showing flexibility and wearability. The exceptional results originate from the PANI's high pseudocapcitance in addition to the wet-spun HA/CNT core fiber's role as a highly conductive and mechanically superior base material. This work shows the suitability of HA/CNT/PANI fibers as supercapacitor electrodes for applications in flexible and wearable electronics. Graphical abstract: Image 1